Capsaicin 8% Patch Untuk Terapi Alternatif Pada Nyeri Neuropati Diabetikum Perifer - Muhammad Luthfi Adnan (WMJ (Warmadewa Medical Journal), 2021)
Abstract Diabetes is one of the most common health problems due to its high incidence and complications. One of the complications associated with diabetes is painful diabetic peripheral neuropathy (PDPN). The capsaicin 8% patch is a localized pain treatment that provides effective pain relief from a single application in patients with peripheral neuropathic pain. The aim of this review is to discuss the effect of capsaicin patch 8% in patients with painful diabetic peripheral neuropathy. The search strategy was conducted in PubMed and modified for other databases. The search was limited to English-language reports. The keywords used were "capsaicinâ€, "capsaicin patch", "painful diabetic peripheral neuropathy", and "pain management". The inclusion criteria used were randomized controlled trials (RCTs), clinical trials or another interventional analysis with full text in English with publications less than the last 10 years. The exclusion criteria used were a review, systematic review, or meta-analysis, studies that were not conducted in humans and non-full text in English with publications over the last 10 years. Results: There are 2 full-text that meet inclusion criteria. From articles related to studies that have been conducted, the use of capsaicin 8% patch can reduce pain, improve nerve function and quality of life in PDPN patients. The use of capsaicin 8% patch has the advantage to pain relief for patients with painful diabetic peripheral neuropathy. Keywords: Alternative therapy, Capsaicin 8% Patch, Diabetes complications, Pain Relief, Painful Diabetic Peripheral Neuropathy, topical drugs